Grace is greater eaudiobook God's plan to overcome your past, redeem your pain, and rewrite your story. - Idleman, Kyle (christianaudio, 2017)
The writer of the letter to the Hebrews said, "See to it that no one misses the grace of God." Over the centuries much ink has been spilled on the subject of grace. Yet perhaps nothing is as hard to explain as God's grace. It doesn't make sense. It's not fair. It can't possibly cover over what I've done. The best way—perhaps the only real way—to understand it is to experience it. But too often in our churches we're not getting grace across and grace is not experienced. Bestselling author and pastor Kyle Idleman wants everyone to experience the grace of God. Through the powerful medium of story, Grace Is Greater leads readers past their hang-ups toward an understanding of grace that is bigger than our mistakes, our failures, our desire for revenge, and our seemingly impossible situations. No sin is so great, no bitterness so deep that God's grace cannot transform the heart and rewrite the story. Perfect for individuals and also for small groups and church-wide studies, Grace Is Greater will help readers truly grasp God's grace, even if the Christians around them have failed to live it.